The intertwining of Zn-finger motifs and abiotic stress tolerance in plants: Current status and future prospects - Moulick, Debojyoti; Bhutia, Karma Landup; Sarkar, Sukamal; Roy, Anirban; Mishra, Udit Nandan; Pramanick, Biswajit; Maitra, Sagar; Shankar, Tanmoy; Hazra, Swati; Skalicky, Milan; Brestic, Marian; Barek, Viliam; et al. (Frontiers in Plant Science, 2023)
Environmental stresses such as drought, high salinity, and low temperature can adversely modulate the field crop’s ability by altering the morphological, physiological, and biochemical processes of the plants. It is estimated that about 50% + of the productivity of several crops is limited due to various types of abiotic stresses either presence alone or in combination (s). However, there are two ways plants can survive against these abiotic stresses; a) through management practices and b) through adaptive mechanisms to tolerate plants. These adaptive mechanisms of tolerant plants are mostly linked to their signalling transduction pathway, triggering the action of plant transcription factors and controlling the expression of various stress-regulated genes. In recent times, several studies found that Zn-finger motifs have a significant function during abiotic stress response in plants. In the first report, a wide range of Zn-binding motifs has been recognized and termed Zn-fingers. Since the zinc finger motifs regulate the function of stress-responsive genes. The Zn-finger was first reported as a repeated Zn-binding motif, comprising conserved cysteine (Cys) and histidine (His) ligands, in Xenopus laevis oocytes as a transcription factor (TF) IIIA (or TFIIIA). In the proteins where Zn2+ is mainly attached to amino acid residues and thus espousing a tetrahedral coordination geometry. The physical nature of Zn-proteins, defining the attraction of Zn-proteins for Zn2+, is crucial for having an in-depth knowledge of how a Zn2+ facilitates their characteristic function and how proteins control its mobility (intra and intercellular) as well as cellular availability. The current review summarized the concept, importance and mechanisms of Zn-finger motifs during abiotic stress response in plants.